2023
DOI: 10.1097/shk.0000000000002159
|View full text |Cite
|
Sign up to set email alerts
|

Severe burn-induced mitochondrial recruitment of calpain causes aberrant mitochondrial dynamics and heart dysfunction

Abstract: Mitochondrial damage is an important cause of heart dysfunction after severe burn injury. However, the pathophysiological process remains unclear. This study aims to examine the mitochondrial dynamics in the heart and the role of μ-calpain, a cysteine protease, in this scenario. Rats were subjected to severe burn injury treatment, and the calpain inhibitor MDL28170 was administered intravenously 1 h before or after burn injury. Rats in the burn group displayed weakened heart performance and decreased mean arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(70 reference statements)
0
2
1
Order By: Relevance
“…Furthermore, these results corroborate the point that modi cation of transcription factor activity is an important step to trigger mesenchymal transition. However, the results are in contrast to our previous ndings showing an accumulation of µ-calpain in the plasma membrane and mitochondria after stressful stimulation [14,15]. Thus, the unidenti ed regulator, which is in charge of the trajectory of µcalpain, warrants to be elucidated.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, these results corroborate the point that modi cation of transcription factor activity is an important step to trigger mesenchymal transition. However, the results are in contrast to our previous ndings showing an accumulation of µ-calpain in the plasma membrane and mitochondria after stressful stimulation [14,15]. Thus, the unidenti ed regulator, which is in charge of the trajectory of µcalpain, warrants to be elucidated.…”
Section: Discussioncontrasting
confidence: 94%
“…µ-calpain is a superfamily of Ca 2+ -dependent nonlysosomal cysteine protease, which consist of a large catalytic subunit, namely calpain 1 (CAPN1) and a small regulatory subunit CAPN4 [13]. We and others have demonstrated that CAPNs participate in a variety of pathophysiological processes, i.e., plasma membrane disruption, mitochondrial damage, transform of vascular permeability and cell motility [14][15][16][17]. Of note, µ-calpain is implicated in the progression of IPF patients [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This susceptibility to mutations results in significant heteroplasmy of mitochondria. Although mitochondrial damage, metabolic dysfunction, and ROS burden have been described in multiple tissues after thermal injury in animal models (15–20), we do not know how it relates to mtDNA mutation burden and immune function after thermal injury in pediatric patients. Accordingly, we sought to determine whether changes in extracellular mtDNA content and mutation load are associated with changes in inflammatory response and innate and adaptive immune function in a cohort of pediatric patients after thermal injury.…”
Section: Introductionmentioning
confidence: 99%